Color and discursive identities in the temple of the Santa Barbara in Tunja - Rojas Rojas, Lizeth (Universidad de Boyacá, 2020)
This article of scientific and technological research presents the results of two investigations related to the discursive identities and operations of semiotic and discursive construction of the mural painting of the Temple of Santa Barbara in Tunja. From the theoretical and methodological perspective of the semiotics of the School of Paris, the relationship between the colors of the paintings and the discursive identities enunciated in the murals of the cited temple was analyzed. It should be noted that the identities of cultural subjects and groups are proposed as multidimensional discursive signs, constituted by their cognition, axiology, passions and semiotic systems, including chromatic ones. The semiotic analysis of the color in the mural painting allowed concluding on the enunciation of discursive identities that hybridize forms of Catholic life, of western European origin, and Native Americans. Similarly, it was agreed that the identified color meanings, dating from the seventeenth century, remain until today in the cultural universe of religious ritual space location.